Factors Affecting Therapeutic Compliance among the Patients with Rheumatic Heart Disease in Bangladesh - Farzana, Kakon; Faruque, Mohammad Omar; Zareen, Salma; Choudhury, Kamrun Nahar; Hossain, Ahmed (Cardiovascular Journal, 2018)
Background: Acute rheumatic fever (ARF) can recur as a result of subsequent Group A Streptococcus (GAS) infections and each recurrence can worsen Rheumatic heart disease (RHD) that has evoked a substantial disease burden in developing countries, including Bangladesh. The objective of this study was to determine the penicillin compliance for rheumatic fever patients. Methods: A matched cross sectional study was conducted among 160 patients in National Center for the Control of Rheumatic Fever and Heart Diseases (NCCRF/HD), Dhaka. Data was collected on face-to-face interview using a standard structured questionnaire about socio-demographic, clinical and behavioral factors. Descriptive and multivariate logistic regression analyses were used to analyze the data. Results: The multiple logistic regression analyses indicated that duration of diagnosis>5 beyond the duration of diagnosis <5 years (OR=2.484, CI=1.170-5.421), age (OR=0.548,CI=0.217-0.574), sex (OR=0.916, CI=0.422-1.964), education (OR=1.963, CI= 0.737-05.361), marital status(OR=0.700, CI=0.272-1.774), fathers education (OR=0.482 CI=0.176 -1.279) and family member (OR= 0.619 CI= 0.2 97 -1.261) were significantly or almost significantly associated with RHD status. Conclusion: In this study, the identified risk groups for rheumatic heart disease reflect a complex interaction between socioeconomic conditions and chronic disease status. Interventions focused on education and poverty will undoubtedly be useful, but not sufficient. Rheumatic heart disease control would benefit from a collaboration of broad public health activities aimed at the prevention and control other chronic diseases. The integration of rheumatic heart disease control activities with non communicable disease programme is crucial in Bangladesh. Cardiovasc. j. 2018; 10(2): 180-185